(untitled) (Damascus University Journal for the basic sciences, 2025)
A quantitative and biostratigraphical study is prepared by using the calcareous nannofossils for the sediments of Eocene in Safa section in the southern west part of Palmyra chain to identify their ages and investigate the paleo-ecological changes characterized the Eocene sediments. Nine bioevents are identified in these sediments (the last occurrence (LO) of eight species: Praeprinsius tenuiculus, Neochiastozygus perfectus Discoaster kupperi, Cribrocentrum reticulatum, Sphinolithus stellatus, Neochiastozygus modestus, Chiasomalithus grandis, Chiasomalithus solitus, and the first occurrence (FO) of Cribrocentrum reticulatum. The biostratigraphical correlation with the western Mediterranean basin gave the presence of diachronism in the bioevents of appearance and disappearance of some species like Cribrocentrum reticulatum, the absence of NNTe10 biozone cause the absence of its index species (Sphinolithus furcatolithaides, Helicosphera comacta, Helicosphera reticulate, Blackites gladius) in Safa section. The retreat of mathematic quantitative data of percentage changes of climatic index species of calcareous nannofossils indicate that the seawater was colder during the Eocene with general cooling trend toward the middle/upper Eocene boundary. The principal components analysis method was used to determine the essential environmental factors that characterized the Eocene period, indicating the presence of two primary factors. The first factor is related to changes in sea water level, while the second factor corresponds to changes in sea water temperature.